Thyroid metastasis from ovarian clear cell carcinoma - Rika Sasaki; Haruhiko Yamazaki; Eita Kumagai; Soji Toda; Aya Saito (Endocrinology, Diabetes & Metabolism Case Reports)
A 56-year-old woman with cervical pain with a history of ovarian clear cell carcinoma stage IIIC was admitted to a primary care doctor. Ultrasonography revealed a microhyperechoic nodule in the thyroid gland and cervical lymph node enlargement, and fine-needle aspiration was performed. The results showed malignancy, and she was admitted to our hospital. The differential diagnoses included primary thyroid neoplasms and thyroid metastases from ovarian clear cell carcinoma. A needle biopsy of the thyroid gland was performed. Immunohistochemistry revealed that the tumor cells were positive for cytokeratin AE1/AE3, hepatocyte nuclear factor-1-beta and PAX8 and negative for thyroglobulin and thyroid transcription factor-1. Therefore, we diagnosed the patient with thyroid metastasis from ovarian clear cell carcinoma. There were no compressive symptoms at the time of the visit to our hospital, and surgery was considered unnecessary. Systemic treatment for ovarian clear cell carcinoma was continued. Three months later, she died of a stroke due to Trousseau’s syndrome.